USING VINAY AND DARBELNET MODEL TO COMPARE MAJOR TYPES OF TRANSLATION BETWEEN INDONESIAN AND ENGLISH: WHEN LEXICOLOGY, STRUCTURE AND CULTURE - mahmud; Wirabhakti, Agus (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to analyze and to describe the sentence structure differences between English and Indonesian language as well as the procedures of translation in text Osaka from Garuda Magazine and Sekilas Musim di Korea. The translation strategies employed, and how to find out the form and the occurrences of those translation procedures which were proposed by Vinay and Darbelnet. Major types of translation procedures have been identified, which are literal translation, calque, borrowing, reduction, adapting, and transposition. This research uses a qualitative approach in which data analysis and interpretation occur. The result of data analysis shows that some of the procedures proposed by Vinay and Darbelnet occured and the sentence structure differences can be identified within the source and the target language. The data are translated using translation procedures and reveals that various and appropriate techniques will result to better translation quality.